NSD2 is a conserved driver of metastatic prostate cancer progression. Issue 1 (December 2018) - Aytes, Alvaro; Giacobbe, Arianna; Mitrofanova, Antonina; Ruggero, Katia; Cyrta, Joanna; Arriaga, Juan; Palomero, Luis; Farran-Matas, Sonia; Rubin, Mark; Shen, Michael; Califano, Andrea; Abate-Shen, Cory
Abstract Deciphering cell-intrinsic mechanisms of metastasis progression in vivo is essential to identify novel therapeutic approaches. Here we elucidate cell-intrinsic drivers of metastatic prostate cancer progression through analyses of genetically engineered mouse models (GEMM) and correlative studies of human prostate cancer. Expression profiling of lineage-marked cells from mouse primary tumors and metastases defines a signature of de novo metastatic progression. Cross-species master regulator analyses comparing this mouse signature with a comparable human signature identifies conserved drivers of metastatic progression with demonstrable clinical and functional relevance. In particular, nuclear receptor binding SET Domain Protein 2 (NSD2 ) is robustly expressed in lethal prostate cancer in humans, while its silencing inhibits metastasis of mouse allografts in vivo. We propose that cross-species analysis can elucidate mechanisms of metastasis progression, thus providing potential additional therapeutic opportunities for treatment of lethal prostate cancer. Identifying cell intrinsic mechanisms promoting metastasis are necessary to develop new cancer therapeutics. Here they do cross-species computational analysis and identify nuclear receptor bindingSET domain Protein 2 (NSD2) as a driver of prostate cancer metastasis.